Tingkat Motivasi Belajar terhadap Hasil Belajar Calon Karyawan Perhutani Group tahun 2023 - Sabria, Shely Sheema (Jurnal Empati Bimbingan dan Konseling, 2024)
Learning motivation can be used as a reference in developing learning outcomes in order to achieve maximum results and as expected. Researchers took this research because to find out how high a person's learning motivation level is, this is considered important because a person's learning motivation level differs from one another. The method used in this research is a quantitative method while using a survey approach with a research design that is a descriptive survey design. In carrying out this research, as many as 60 items were compiled from the development of several indicators that had been selected after carrying out the process of evaluating the items by the examiners and having carried out validity and reliability tests. The results obtained that as much as 70% of the subjects have a high level of motivation to learn.Keywords: motivation,learning,Perhutani